A novel integrated daylighting system for optimal daylight performance in office buildings - Aljudaiy, Fawzan (2022)
The thesis assessed the potential of optimising the daylight performance for an office building in Riyadh city, Saudi Arabia, by means of a novel passive daylighting system that can achieve balanced daylighting performance. The function of the proposed system is to prevent and mitigate the negative impact of direct sunlight inside the building by reducing the illuminance level in the front area while increasing it in the deep area of the space. The aim was to reduce the annual level of sunlight exposure (ASE) while increasing the daylight autonomy (DA), the useful daylight illuminance (UDI) and the daylighting uniformity at the work plane. This aim was achieved through four objectives, to assess the current situation of the daylighting performance for typical office space, to invent a novel integrated daylighting system that can enhance the daylighting performance, to optimise the design of the proposed system and finally to assess the daylighting performance of the proposed system.